Spatial Resilience Modelling of Merapi Volcano Ecosystem Post-Eruption - Emma Soraya; Wahyu Wardhana; Ronggo Sadono (Jurnal Ilmu Kehutanan)
The ability of volcano ecosystem to recover post an eruption to the pre eruption status is affected by its ecological resilience. Resilience of an ecosystem can be defined as the ability of an ecosystem to bounch back after (a) disturbance(s). This study aimed to model spatial resilience of Merapi volcano ecosystem within the area of National Park of Merapi Volcano (TNGM) five years post 2010 eruption and restoration intervention. Analysis was conducted using multi temporal remote sensing and spatial analysis using geographic information system to draw the changes of the ecosystem over time, particularly post eruption and restoration actions. The modelling resulted that five years post eruption, there was resilience transisition/ recovery in volcano ecosystem in TNGM post 2010 eruption. The resilience was shown by the changes from open area to vegetation covers as grass, shrubs, and secondary forests. The transitions occured in term of natural succession as well as human intervention in restoration programs. However, the success of restoration actions to recover the ecosystem to the pre eruption status was not always able to be detected within the period of five years post eruption.